Contemporary genetic structure reflects historical drainage isolation in an Australian snapping turtle, Elseya albagula. (29th August 2013) - Todd, Erica V.; Blair, David; Farley, Sharon; Farrington, Lachlan; FitzSimmons, Nancy N.; Georges, Arthur; Limpus, Colin J.; Jerry, Dean R.
Abstract : Effective spatial classification of freshwater biodiversity remains a worldwide conservation challenge. The isolating nature of catchment boundaries over evolutionary timescales makes them potentially important in defining natural units for biodiversity management. We sought to clarify biogeographical relationships amongst drainages within Australia's biodiverse mid‐eastern coastal region (Fitzroy, Burnett, and Mary Catchments) where freshwater communities face considerable urban pressure, using a locally endemic riverine specialist, the white‐throated snapping turtle, E lseya albagula . Mitochondrial and nuclear microsatellite data sets were employed to investigate past and present influences on population connectivity and to identify units for management. Populations within catchments were largely well connected genetically. However, the Fitzroy Catchment contained a distinct genetic lineage, deeply divergent from a second lineage present across the Burnett and Mary Catchments. The two lineages can be considered evolutionarily significant units that reflect historical isolation of the Fitzroy and recent coalescence of the Burnett‐Mary Catchments during lowered Pleistocene sea levels. Congruence with geological evidence and patterns reported for fish and macroinvertebrates supports a shared biogeographical history of a diverse regional biota. This work highlights the need for better spatial classification of freshwater biodiversity at local as well as regional scales, including recognition of potentially cryptic diversity amongst individual river drainages. © 2013 The Linnean Society of London